The Leadership Challenge: Improving Learning in Maltese Schools - Christopher G. Bezzina (MDPI AG, 2024)
This reflective paper aims to contextualise the notion of leadership and professional learning within the Maltese context and present the challenges that the country faces if it truly wants to improve the level of learning in our schools. It presents the main challenge that the country faces at the conceptual, policy and institutional levels as the country needs to grapple with our understanding of governance and how this has been addressed over the years. It is argued that through such an engagement can we relate to the notion of leadership and being a leader in Maltese schools. The paper will explore the role that leadership and governance have on the way we view reform and the nurturing of professional learning and development in Maltese schools. The position taken is that central to any changes requires exploring the need to nurture trust as a fundamental principle that governs the way we relate at both systems and school level. Unless a change in mindset is adopted few changes will leave an impact where it truly matters, student learning.